Influence of localised surface plasmons on energy transfer between quantum dots - Gounko, Iouri; Bradley, Louise (IEEE Computer Society, 2010)
The effects of surface plasmons (SPs) on Forster resonant energy transfer (FRET) in colloidal quantum dot (QD) structures have been investigated. CdTe QDs of two different sizes acted as donors and acceptors in a mixed donor-acceptor monolayer on top of a gold nanoparticle layer and an acceptor-gold-donor sandwich structure. The structures were prepared by a layer-by-layer technique and characterized by absorption and photoluminescence (PL) spectroscopy as well as time-resolved PL measurements. For the case of the mixed QD monolayer a recovery of the acceptor emission is observed when increasing the acceptor-gold separation. The reduction of the donor lifetime indicates that the FRET process is enhanced by 30%. In the sandwich structure a clear modification of the FRET distance dependence towards a typical SP influenced dependence on the QD-gold separation is observed. The maximum acceptor QD emission occurs at approximately 12 nm from the intermediate gold layer, corresponding to a donor-acceptor separation at which no FRET is observed in structures without gold. By varying the gold concentration the acceptor PL enhancement can be increased and an absolute enhancement of 25% compared to structures without gold is achieved.
12th International Conference on Transparent Optical Networks (ICTON), 2010
PUBLISHED
Munich
Keywords: Optics; Forster resonant energy transfer (FRET); semiconductors